Facebook in Building Social Capital: A Study of Malaysia College Students - Chuah, Soo Fei (2010)
The main purpose of this study is to examine the relationship between social capital, self-esteem, life satisfaction and the use of Facebook. A survey was conducted in Universiti Utara Malaysia to examine the relationship between bonding and bridging social capital, degrees of a person self-esteem and life satisfaction and intensity of Facebook use. 230 questionnaires were distributed to undergraduate Communication students and 224 questionnaires were collected. The results of the research showed that there are positive relationship between bonding social capital, bridging social capital, self-esteem and the intensity of Facebook use, with the strongest relationship being to self-esteem. However, the results showed that there is no significant relationship between the degrees of a person’s life satisfaction and the intensity of Facebook use.